Como adolescentes apreendem a ciência e a profissão de cientista? - REZNIK, Gabriela (Universidade Federal do Pará, 2018)
The media representations play an important role on the perception of girls toward the scientific universe. In this paper, we seek to understand perceptions of female teenagers about science and scientists, using as stimulus TV stories from Jornal Nacional and Fantástico, of Rede Globo. We held four focus groups with students of the 2nd year of high school of public and private schools. Among the visions of the scientific activity we highlight: the association of science to the contents of school disciplines offered in elementary and secondary school; the association of science with experimentation and discovery; the vision of science as accumulation of knowledge as linear growth. We have not identified clear differences in perceptions of teenagers from different social classes. By using a qualitative approach - little explored in studies on public perceptions of S&T - this study may contribute to a deeper understanding of the perception of teenagers toward the scientific activity.